The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1517/14712598.2015.1025045
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and effectiveness of anti-HBV therapy with early withdrawal of HBIG prophylaxis to prevent HBV recurrence following liver transplantation

Abstract: Patients who are considered low risk for HBV recurrence at the time of liver transplant may safely be able to utilize a short-term duration of HBIG with indefinite antiviral maintenance therapy afterwards, whereas high-risk patients will likely need long-term HBIG in combination with antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These recent data strengthen the findings of previous studies, which supported the efficacy of antiviral monotherapy with a high‐genetic barrier NA against post‐LT HBV recurrence after HBIG withdrawal 65‐67 . However, for LT recipients with higher risk of HBV recurrence, such as patients with HBV DNA positivity at LT or HCC pre‐LT, a decision for HBIG discontinuation should be taken with great caution and after ensuring close monitoring, while further studies are needed for the evaluation of safety of HBIG discontinuation in such patients 68 …”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 98%
“…These recent data strengthen the findings of previous studies, which supported the efficacy of antiviral monotherapy with a high‐genetic barrier NA against post‐LT HBV recurrence after HBIG withdrawal 65‐67 . However, for LT recipients with higher risk of HBV recurrence, such as patients with HBV DNA positivity at LT or HCC pre‐LT, a decision for HBIG discontinuation should be taken with great caution and after ensuring close monitoring, while further studies are needed for the evaluation of safety of HBIG discontinuation in such patients 68 …”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 98%
“…Several studies have shown that LT recipients who were switched to ETV or TDF monoprophylaxis 6-12 months after commencing a combination of HBIG and ETV or TDF therapy had low rates of detectable HBV DNA levels [721,[725][726][727][728]. However, for LT recipients with a higher risk of HBV recurrences, such as patients with HBV DNA positivity at LT or HCC pre-LT, a decision for HBIG discontinuation should be taken with great caution and after ensuring close monitoring, while further studies are needed for the evaluation of the safety of HBIG discontinuation in such patients [729].…”
Section: Prophylaxis For Hbv Recurrencementioning
confidence: 99%